Pharmacological insights into Ipomoea staphylina: Therapeutic activities and the isolated bioactive metabolic compounds (Mongolian Journal of Chemistry, 2024)
This review comprehensively explores I. staphylina's traditional uses, diverse applications, and pharmacological activities. Extensively used in traditional medicine, this plant addresses a range of ailments, including stomach disorders, respiratory issues, and rheumatism. Research has highlighted its significant antimicrobial, anti-inflammatory, antioxidant, antidiabetic, anthelmintic, and analgesic properties. Notably, its antiulcer activity highlights its potential as a novel antiulcer agent, while hepatoprotective and nephroprotective effects suggest therapeutic applications in liver and kidney disorders. Studies on its anti-diabetic potential show significant reductions in blood glucose levels and positive impacts on biochemical markers. The plant's anti-mutagenic activity against base-pair mutations expands its potential applications. The review also discusses the isolation and pharmacological applications of pure compounds identified through LC-MS and NMR analyses. This review identifies I. staphylina as a promising source of bioactive compounds with therapeutic potential, emphasizing the need for further research to isolate and characterize its active constituents.